KONTROL PEREMPUAN PADA KEPEMILIKAN SUMBER DAYA YANG LEMAH DALAM USAHA KELUARGA. - Misrin Hariyadi; Badruli M; Siti Salbiyah (BALANCE: Economic, Business, Management and Accounting Journal, 2008)
Understanding the concept of gender as the division of roles of men and women who are socially and culturally constructed, needs to be done in order to realize equality and gender justice. The understanding, necessary to place women as subjects of development, in order to improve the position and role of women in national and state life. This research is done on the women sellers crackers, data collection was done by a written interview. Data were analyzed using the Harvard Gender Analysis Method, to determine the four basic elements: (1) Profile of activity based on gender division of labor, (2) Access Profile, (3) Profile control; (4) Factors related to the things that lead to the distribution of work, the profiles, access and community control. Results obtained in the activity profiles based on gender division of labor, which includes a list of tasks men and women, mothers appear dominant task. Profile access and control over resources within the family, women in a weak position. While in reality, women have the "role and employment" which determines the continuity of family life. For that education and training activities can be provided as one way in order to empower women to be more efficient and effective manner. Kata Kunci : Kontrol, Kepemilikan, Sumber Daya, dan Usaha Keluarga.